1998
DOI: 10.1590/s0074-02761998000200004
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis and other Enteroparasites in Children at Uberlândia City, State of Minas Gerais, Brazil

Abstract: To evaluate the rate of infection by Strongyloides stercoralis and other enteroparasites a survey was conducted in the city of Uberlândia, State of Minas Gerais, Brazil. A total of 900 stool samples from 300 children aging from four months to seven years, randomly selected in ten nursery schools from September 1994 to December 1995 The occurrence of S. stercoralis in children aged from 0-14 years in some Brazilian states is summarized in Table I.This study aimed at surveying the prevalence of S. stercoralis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…The variety of techniques may be noted, but most studies have used techniques suitable for the detection of larval helminths since the suspicion of infection by S. stercoralis could be mentioned in the population studied. The average et al (1994); Gennari-Cardoso et al (1996); Ferreira and Marçal Jr (1997); Machado and Costa-Cruz (1998); Rocha et al (2000); Ribeiro and Marçal Júnior (2003); Barbosa et al (2005) occurrence was 11•8% using parasitological diagnostic methods. In 4 studies of immunosuppression using parasitological and immunological diagnosis it was found that the mean occurrence increased from 7•1% to 19•5% respectively (Paula et al 2000;Schaffel et al 2001;Mendonça et al 2006;Machado et al 2008d), emphasizing the usefulness of serological methods as a tool for diagnosis of strongyloidiasis, especially when the question involved is immunosuppression.…”
Section: Occurrence Of S Stercoralis Infection Associated With Diffementioning
confidence: 96%
“…The variety of techniques may be noted, but most studies have used techniques suitable for the detection of larval helminths since the suspicion of infection by S. stercoralis could be mentioned in the population studied. The average et al (1994); Gennari-Cardoso et al (1996); Ferreira and Marçal Jr (1997); Machado and Costa-Cruz (1998); Rocha et al (2000); Ribeiro and Marçal Júnior (2003); Barbosa et al (2005) occurrence was 11•8% using parasitological diagnostic methods. In 4 studies of immunosuppression using parasitological and immunological diagnosis it was found that the mean occurrence increased from 7•1% to 19•5% respectively (Paula et al 2000;Schaffel et al 2001;Mendonça et al 2006;Machado et al 2008d), emphasizing the usefulness of serological methods as a tool for diagnosis of strongyloidiasis, especially when the question involved is immunosuppression.…”
Section: Occurrence Of S Stercoralis Infection Associated With Diffementioning
confidence: 96%
“…The sample size (n=75) was calculated on the basis of the study of Machado & Costa Cruz (1998). A total of 75 SWPs aged above 18 years participated in the study (29 from RECICLO and 46 from APCORB).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for the preparation of the microscope slides and diagnosis were performed as described in the literature (Machado & Costa Cruz, 1998;Santos et al, 2014). The detection of intestinal helminths or protozoa in the samples by at least one method was considered for the individual diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Entre as doenças parasitárias com maior prevalência no Brasil, a estrongiloidíase vem sendo apontada por vários autores como uma das principais, com prevalência variando de 3% a 82% (Gonçalves et al;Kobayashi et al1995;Kobayashi et al,1996;Machado & Costa-Cruz, 1998;Santos, 2000;Morrone et al, 2004).…”
Section: Introductionunclassified